Peter the Great : a biography - Hughes, Lindsey, 1949-2007 (Yale University Press, 2002)
"This, the shorter biography of Peter the Great (1672-1725), tells his story from birth to death in twelve chapters, including two final chapters on the Tsar's legacy and posthumous reputation up to the present, with the aim of providing a vivid sense of the dynamics of his life and reign: The focus is firmly on the dramatic, appealing and unconventional figure of Peter himself: his actions, deliberations, decisions, relationships, tastes and possessions. It includes the more bizarre aspects of his character, such as his interest in dwarfs, the use of disguises, clowning and vandalism. The main sources are Peter's letters and papers, both published and unpublished, as well as other contemporary accounts and documents." "The narrative comprises both the public and private life, the life Peter lived as well as his significant fantasy world. Hughes offers fascinating new material on the 'alternative' or 'parallel' history of Peter's many disguises and pseudonyms, his deference to a number of mock superiors, and his relationships with individuals such as his second wife Catherine and his favourite Alexander Menshikov." "In each chapter Hughes explores Peter's image in painting and sculpture, bringing the story to the present day with a discussion of controversial monuments in Moscow and St. Petersburg."--Jacket